The Influence of E-Recruitment and E-Selection on Interest in Applying for Jobs at the Central Statistics Agency of Lamongan Regency in the 2024 Statistics Partner Program (Case Study of Generation Z of Lamongan Regency) - Alfianto, Moch. Rizqi; Novitasari, Diah Ayu; Purnomo, Nanto (Formosa Journal of Applied Sciences, 2024)
Based on data from the Lamongan Regency Central Statistics Agency (BPS), the number of applicants for the statistical partner program is 2829 people. This research aims to test whether there is an important impact of e-recruitment and e-selection variables in creating interest in applying for jobs among Gen Z in Lamongan Regency. Primary data in this research was obtained from respondents and measured quantitatively. The information that will be obtained through the survey is 27 statements/questions. This study used a sample of 319 generation Z in Lamongan Regency from 1564 generation Z who had applied for jobs in the 2024 statistical partner program in Lamongan Regency using random sampling techniques. Data analysis in this study was carried out using SPSS software version 26. The findings from this study show that e-recruitment and e-selection factors have a positive influence on a person's interest in applying for a job.